Use of Low Order Models for Near-Optimal Control of High Order Systems - de Bruin, Huibregt (My University, 2015)
Ten different reduced models, of a particular test system are selected. Two cost functions are selected and the test system minimum cost is found for each. The model optimal controls are found for each cost function and are used to provide sub-optimal control of the system using two different methods. The system cost is calculated for each case and compared to the minimum attainable. The reduction methods are compared with a view to application for the near-optimal control of a linear system.
Keywords: high order systems, cost, control, optimal